2014
DOI: 10.1016/j.rgmx.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de vida y grado de satisfacción de pacientes postoperados de funduplicatura de Nissen laparoscópica

Abstract: The level of satisfaction and quality of life obtained were comparable with reported standards; and the residual symptoms after antireflux surgery were easily controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In this study significant improvement in global quality of life was observed as late as 12 months after surgery and remained at this level until the final observation point 24 months after surgery. Other authors reported significant improvement in quality of life as soon as 1 month after surgery [ 18 , 28 , 29 ]. More than 90% of the patients would undergo the surgery again or recommend it [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study significant improvement in global quality of life was observed as late as 12 months after surgery and remained at this level until the final observation point 24 months after surgery. Other authors reported significant improvement in quality of life as soon as 1 month after surgery [ 18 , 28 , 29 ]. More than 90% of the patients would undergo the surgery again or recommend it [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…La popularización de la resolución quirúrgica abierta, y después por mínima invasión, ha permitido la globalización de la funduplicatura laparoscópica, estableciéndose como el estándar de oro en el manejo quirúrgico de ERGE con excelentes resultados y remisión sintomática a largo plazo en 90-95% de los casos. [1][2][3][4][5] El objetivo del tratamiento quirúrgico es restablecer la barrera antirreflujo, proteger la mucosa esofágica evitando el reflujo ácido y la prevención de complicaciones. 6 La funduplicatura se realiza como componente de la barrera antirreflujo; sin embargo, su papel en la prevención de la recurrencia aún no está claro.…”
Section: Introductionunclassified
“…Accordingly, it can help healthcare providers to effectively fulfill patients’ needs, facilitate their recovery, and promote their well-being ( 5 ). Patient’s satisfaction is defined as patients’ attitude toward and judgment about the degree of fulfilling their preferences and expectations by healthcare providers ( 6 - 8 ). In other words, there will be no quality care without patient’s satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, besides hospitalized children, their parents are considered as healthcare clients. As a result, parents’ views can reflect their children’s views ( 8 ). Previous studies reported that patients’ level of satisfaction with healthcare services ranges from 47.1% to 96.7% ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%